2018
DOI: 10.2147/jhl.s172410
|View full text |Cite
|
Sign up to set email alerts
|

Midwife conceptualizations of clinical leadership in the labor ward of district hospitals in KwaZulu-Natal, South Africa

Abstract: BackgroundIn South Africa, inadequately skilled health care providers and poor clinical leadership are continually linked to preventable perinatal and maternal mortality, which calls for improved clinical skills among health care providers and for strong clinical leadership at the bedside. Very little has been done to ensure clinical leadership at the bedside in the labor ward of district hospitals. One strategy implemented has been the appointment of District Clinical Specialist Teams, introduced to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…26 49 50 Visibility is an important relational skill required to ensure optimal patient care. 26 51 52 The shortages of positional clinical leaders makes it difficult for the few available positional clinical leaders to be visible in labour wards and to provide effective clinical leadership. 25 In this study, it was reported that positional clinical leaders struggle to balance between clinical leadership and managerial roles, consistent with other studies.…”
Section: Balance Between Managerial and Leadership Rolesmentioning
confidence: 99%
See 2 more Smart Citations
“…26 49 50 Visibility is an important relational skill required to ensure optimal patient care. 26 51 52 The shortages of positional clinical leaders makes it difficult for the few available positional clinical leaders to be visible in labour wards and to provide effective clinical leadership. 25 In this study, it was reported that positional clinical leaders struggle to balance between clinical leadership and managerial roles, consistent with other studies.…”
Section: Balance Between Managerial and Leadership Rolesmentioning
confidence: 99%
“…50 An environment where all healthcare providers could effectively contribute to patient care was seen to be an essential factor influencing clinical leadership in labour wards. 26 Communication and teamwork facilitate cohesion, development of interpersonal skills of the care team and interprofessional collaboration through discussion and reflection on practice. 56 Midwives expressed that doctors did not value midwives' contribution to patient care, which is at odds with labour wards in district hospitals, where most deliveries are midwife-led.…”
Section: Balance Between Managerial and Leadership Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective leaders need to develop capacities from all three areas. They must be good managers able to guide administrative processes in the ward, in the institution and nationally depending on where they work (USAID 2015 ; Divall 2015 ; Mianda and Voce 2018 ).…”
Section: Leadership Management and Administrationmentioning
confidence: 99%
“…Mianda and Voce ( 2018 ), Jarvis and Reeves ( 2017 ) and Divall ( 2015 ) point out a gap that has persisted in midwifery leadership and clinical leadership. Emphasis has been placed on position leadership to the neglect of leadership on the bedside and in the maternity ward.…”
Section: Definition and The Nature Of Leadershipmentioning
confidence: 99%